Hypercalciuria and recurrent urinary tract infections: incidence and symptoms in children over 5 years of age - ALPAY, HARİKA; GÜRAN, TÜLAY (SPRINGER, 2005)
Hypercalciuria is an important and common risk factor in the formation of renal stones. In this study we evaluated the incidence and the clinical presentation of hypercalciuria in 75 children over 5 years of age with the diagnosis of recurrent urinary tract infection (UTI). We measured random urinary calcium/creatinine value (three times), 24-h urinary calcium excretion, serum calcium, phosphorus, electrolytes, blood gas, blood urea nitrogen and creatinine levels. Hypercalciuria was found in 32 patients (43%). The mean urinary calcium/creatinine ratio for hypercalciuric patients was 0.50 +/- 0.21 mg/mg (min: 0.24, max: 2.60). The mean urinary calcium/creatinine ratio for the rest of the study population-those without hypercalciuria-was 0.10 +/- 0.04 mg/mg (min: 0.01, max: 0.18). Presenting symptoms of the hypercalciuric patients and normocalciuric patients were similar. History of familial urolithiasis was positive in 19 patients (59%). Predisposing urinary tract abnormalities in recurrent UTI was shown in 12 of the hypercalciuric patients (12/32, 37.5%) and 8 of the normocalciuric patients (8/43, 19%) without a statistically significant difference between. We conclude that hypercalciuria is not a rare finding among recurrent UTI cases in Turkish children. Hypercalciuria does not modify the clinical presentation of UTI, and we suggest the investigation of urinary calcium excretion in children with recurrent UTI.
Keywords: child; hypercalciuria; urinary tract infection; IDIOPATHIC HYPERCALCIURIA; CALCIUM EXCRETION; INFANCY; RATIOS